An Ultra‐low Concentration of Gold Nanoparticles Embedded in the NiO Hole Transport Layer Boosts the Performance of p‐i‐n Perovskite Solar Cells. Issue 2 (13th December 2018) - Xiao, Shuang; Xu, Fang; Bai, Yang; Xiao, Junyan; Zhang, Teng; Hu, Chen; Meng, Xiangyue; Tan, Hairen; Ho, Ho‐Pui; Yang, Shihe
Abstract : NiOx is a promising hole transport material for p‐i‐n perovskite solar cells (PVSCs) on account of its high mobility, excellent stability and prospect for large‐scale fabrication. However, the typical conductivity of NiOx is low because of the low carrier concentration, which consequently compromises its photovoltaic performance. Herein, we show that the carrier concentration of NiOx can be improved by as much as three times through embedding a small concentration (0.11 At%) of gold nanoparticles (Au‐NPs), 2–3 nm in diameter, into the NiOx thin film. The enhancement is due to the formation of Ohmic contact between Au and NiOx while avoiding direct contact between Au and perovskite. All key parameters of the PVSC, namely J sc, V oc, and FF have improved, and the overall efficiency shows a significant improvement from 17.8% to 20.2%. The small size, low concentration, and Ohmic contact nature of the embedded Au‐NPs, together with this simple method point to a new promising direction for developing high performance PVSCs. Abstract : Ultra‐low concentration of 2–3 nm gold nanoparticles embedded with an Ohmic contact into a NiOx film triples its hole concentration. This leads to a significant conductivity increase of the NiOx hole transport layer and the consequent decrease of the series resistance of the HTL based perovskite solar cells, pronouncedly improving the efficiency of PVSCs from 17.8 to 20.2%.